Aplicativo para avaliar o nível de conhecimento tático declarativo no handebo - Caldas Souza Leao, I.; Tavares Viana, M.; Botelho Sougey, E. (Revista Ciencia del Deporte, 2017)
The objective was to construct an application test to evaluate the level of declarative tactical knowledge (CTD) of handball athletes. The study was descriptive and transversal with samples for convenience, an application with digital technology (android) was created to evaluate this type of knowledge in this modality. The study was approved by the ethics committee of CCS - UFPE under the protocol Nº 94.896, 08/14/2012. The Tactical Declarative knowledge test in Handball was registered in Brazil as a computer program under the number BR 51 2015 000042-0; National Institute of Industrial Property. The said application was constructed from the agreement of the answers of experts of the high level of the Brazilian handball that were interviewed. From the analysis of 60 video scenes, 11 agreed, the application was built. After the agreement of the experts' answers, an application was developed that measures the level of CTD in handball. This test favors greater reliability of athletes' responses to this sport; the same evaluates levels of CTD (perception and decision making) and reaction time in real time.